Determination of Technical and Economic Indicators of Road Construction Machines - Toychiyev Khasanboy Tokhir ugli; Toychiyev Khusanboy Tokhir ugli; Bakirov Lutfillo Yuldoshaliyevich, PhD (Zien Journals, 2023)
The technical and economic indicators of road construction machines are studied in this article. Constructive-accounting performance (Pk-h), technical performance (Pt), and operational performance (Pe) were determined
Keywords: constructive-calculation work efficiency; technical work efficiency